Bourbons, landowners and royal justice in Piura at early 19th century The life history of a free ‘zambo pardo’, overwhelmed by love affairs, judges and envies of blacks, zambos and mulattos - Espinoza Claudio, César (2017)
A reading and examination of a criminal-judicial process located in Piura’s Regional Archive allows us to reconstruct the life his-tory of a ‘zambo pardo’. This manuscript let us acknowledge legislation and function of Bourbon judicial bureaucracy related to an afrodescendant’s legal claim for respect of his civil rights. In a historical context of war between Spain and Great Britain, an english naval assault takes place at the port of Payta (1805) that mobilizes the viceroyal authorities. In Piura’s city an increasing fear explodes, related to afrodescendant population that could join this english armed assault, making judges being obliged to display every legal and physical force to execute ‘public and exemplary’ punishment to black people who attacked Isidoro Gorrichátegui, a ‘zambo pardo’, known as a successful merchant with deals between Piura and Panama, but also because he was living overwhelmed by his love failures in conquering the affection of a ‘mulatilla’.